Fluorine-containing copolymer
By adjusting the content of different units in the fluorine-containing copolymer and controlling the melt flow rate and number of functional groups, a fluorine-containing copolymer with durability and transparency at high temperature was prepared, which solved the problem that the molded body lost its deformation resistance and ozone resistance at high temperature in the prior art, and achieved the effect of low permeability of the medicinal liquid and poor dissolution of fluorine ions.
Patent Information
- Application Number
- CN202380052176.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-26
- Filing Date
- 2023-07-13
- Publication Date
- 2025-03-14
AI Technical Summary
The existing fluorine-containing copolymers lose their deformation resistance and ozone resistance at high temperatures, and it is difficult to obtain a beautiful molded body by injection molding. At the same time, there are problems with liquid permeability and fluorine ion dissolution.
A new fluorine-containing copolymer was prepared by adjusting the content of tetrafluoroethylene, hexafluoropropylene and fluoro (alkyl vinyl ether) units in the fluorine-containing copolymer, as well as controlling the melt flow rate and the number of functional groups. The copolymer has a hexafluoropropylene unit content of 8.6% to 11.9%, a fluoro (alkyl vinyl ether) unit content of 0.5% to 1.9%, and a melt flow rate of 4.6 g/10 minutes to 14.4 g/10 minutes under 372°C.
It realizes durability for bending, compression and tensile loads at high temperatures, maintains good transparency and ozone resistance, and reduces the permeability of the medicinal liquid and the dissolution of fluoride ions, which is suitable for preparing beautiful molded bodies by injection molding.
Smart Images

Figure BDA0005229902170000071 
Figure BDA0005229902170000201 
Figure BDA0005229902170000291
Abstract
Description
Technical Field
[0001] The present invention relates to fluorine-containing copolymers. Background Art
[0002] Patent Document 1 describes a terpolymer containing, in the form of a copolymer, (a) tetrafluoroethylene, (b) about 4% to about 12% by weight of hexafluoropropylene based on the weight of the terpolymer, and (c) about 0.5% to about 3% by weight of perfluoro(ethyl vinyl ether) or perfluoro(n-propyl vinyl ether) based on the weight of the terpolymer.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 52-109588 Summary of the invention
[0006] Problems to be solved by the invention
[0007] An object of the present invention is to provide a fluorine-containing copolymer which can be molded by injection molding to obtain a beautiful injection-molded product, and which can obtain a molded product having excellent transparency, deformation resistance to a bending load applied at 150°C, deformation resistance to a compressive load applied at 70°C, durability to a tensile force applied at 150°C, ozone resistance, solvent crack resistance, low permeability to chemical liquids, and resistance to fluorine ions eluting into chemical liquids.
[0008] Means for solving problems
[0009] According to the present invention, a fluorinated copolymer is provided, which is a fluorinated copolymer containing tetrafluoroethylene units, hexafluoropropylene units and fluoro(alkyl vinyl ether) units, wherein the content of the hexafluoropropylene units is 8.6% to 11.9% by mass relative to all monomer units, the content of the fluoro(alkyl vinyl ether) units is 0.5% to 1.9% by mass relative to all monomer units, the melt flow rate at 372°C is 4.6 g / 10 min to 14.4 g / 10 min, and the total amount of -CF2H, carbonyl-containing terminal groups, -CF=CF2 and -CH2OH is 0.5% to 1.9% by mass relative to all monomer units. 6 The number of carbon atoms in the main chain is less than 90.
[0010] Effects of the Invention
[0011] According to the present invention, there can be provided a fluorine-containing copolymer which can be molded by injection molding to obtain a beautiful injection-molded product, and which can obtain a molded product having transparency, deformation resistance to a bending load applied at 150° C., deformation resistance to a compressive load applied at 70° C., durability to a tensile force applied at 150° C., ozone resistance, solvent crack resistance, and excellent low permeability to chemical liquids, and which is not prone to elution of fluorine ions into chemical liquids. DETAILED DESCRIPTION
[0012] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.
[0013] The fluorine-containing copolymer of the present invention contains tetrafluoroethylene (TFE) units, hexafluoropropylene (HFP) units and fluoro(alkyl vinyl ether) (FAVE) units.
[0014] As fluororesins, non-melt-processable fluororesins such as polytetrafluoroethylene (PTFE) and melt-processable fluororesins are known. PTFE has excellent properties, but has the disadvantage that melt processing is extremely difficult. On the other hand, as melt-processable fluororesins, TFE / HFP copolymers (FEP), TFE / PPVE copolymers (PFA) and the like are known, but have disadvantages such as poor heat resistance compared to PTFE. Therefore, in Patent Document 1, the above-mentioned terpolymer is proposed as a fluorocarbon polymer that improves these disadvantages.
[0015] However, compared with the fluorinated copolymers of the past such as the ternary copolymers described in Patent Document 1, fluorinated copolymers with excellent transparency are required. In particular, for piping components such as valves, joints, nuts, and flowmeters, high transparency is required in order to be able to visually observe the state of the liquid medicine in the piping components. In addition, the liquid medicine piping is required to have the following characteristics: it is difficult to deform even when subjected to a bending load at high temperature, it is difficult to deform even when subjected to a continuous load compression load for a long time, and it is difficult to break even when subjected to a tensile force at high temperature. Furthermore, it is of course required to have durability to reactive fluids such as ozone and chemicals, and low permeability to liquid medicines such as ammonia.
[0016] It was found that by adjusting the contents of HFP units and FAVE units, the melt flow rate and the number of functional groups of the fluorinated copolymer containing TFE units, HFP units and FAVE units within extremely limited ranges, a molded product having excellent transparency, deformation resistance to a bending load applied at 150°C, deformation resistance to a compressive load applied at 70°C, durability to a tensile force applied at 150°C, ozone resistance, solvent crack resistance, and low permeability to a liquid medicine such as aqueous ammonia can be obtained. Furthermore, by molding the fluorinated copolymer of the present invention by injection molding, a beautiful injection molded product can be obtained.
[0017] The fluorinated copolymer of the present invention is a melt-processable fluororesin. Melt-processability means that the polymer can be melted and processed using existing processing machines such as an extruder and an injection molding machine.
[0018] Examples of FAVE constituting the FAVE unit include those selected from the general formula (1):
[0019] CF2=CFO(CF2CFY 1 O) p -(CF2CF2CF2O) q -Rf (1)
[0020] (Where Y 1 represents F or CF3, Rf represents a perfluoroalkyl group having 1 to 5 carbon atoms, p represents an integer of 0 to 5, and q represents an integer of 0 to 5. ) and the general formula (2):
[0021] CFX=CXOCF2OR 1 (2)
[0022] (wherein, X is the same or different and represents H, F or CF3, R 1 It represents a linear or branched fluoroalkyl group having 1 to 6 carbon atoms which may contain 1 to 2 atoms of at least one kind selected from the group consisting of H, Cl, Br and I, or a cyclic fluoroalkyl group having 5 or 6 carbon atoms which may contain 1 to 2 atoms of at least one kind selected from the group consisting of H, Cl, Br and I. At least one of the group consisting of monomers represented by ).
[0023] Among them, as the above-mentioned FAVE, the monomer represented by the general formula (1) is preferred, more preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) (PEVE) and perfluoro(propyl vinyl ether) (PPVE), further preferably at least one selected from the group consisting of PEVE and PPVE, and particularly preferably PPVE.
[0024] The content of the HFP unit in the fluorinated copolymer is 8.6% to 11.9% by mass relative to the total monomer units, preferably 8.8% by mass or more, more preferably 9.1% by mass or more, further preferably 9.6% by mass or more, further preferably 9.8% by mass or more, particularly further preferably 10.0% by mass or more, particularly preferably 10.2% by mass or more, and most preferably 10.4% by mass or more, preferably 11.7% by mass or less, more preferably 11.5% by mass or less, further preferably 11.4% by mass or less, further preferably 11.2% by mass or less, particularly further preferably 11.0% by mass or less, particularly preferably 10.7% by mass or less, and most preferably 10.4% by mass or less. When the content of the HFP unit is too small, a molded product having excellent transparency and solvent crack resistance cannot be obtained. When the content of the HFP unit is too large, a molded product having excellent deformation resistance to a bending load applied at 150° C. and excellent deformation resistance to a compressive load applied at 70° C. cannot be obtained.
[0025] The content of the FAVE unit of the fluorinated copolymer is 0.5% to 1.9% by mass relative to all monomer units, preferably 0.6% by mass or more, more preferably 0.7% by mass or more, further preferably 0.8% by mass or more, particularly preferably 0.9% by mass or more, most preferably 1.0% by mass or more, preferably 1.7% by mass or less, more preferably 1.6% by mass or less, further preferably 1.5% by mass or less, further preferably 1.4% by mass or less, particularly preferably 1.3% by mass or less, particularly preferably 1.2% by mass or less, and most preferably 1.0% by mass. When the content of the FAVE unit is too small, a molded body having excellent transparency, durability to a tensile force applied at 150°C, ozone resistance, and solvent crack resistance cannot be obtained. When the content of the FAVE unit is too much, a molded body having excellent low permeability to a drug solution such as deformation resistance to a bending load loaded at 150°C, deformation resistance to a compressive load loaded at 70°C, and low permeability to ammonia cannot be obtained.
[0026] The content of the TFE unit of the fluorinated copolymer is preferably 86.2% by mass or more relative to all monomer units, more preferably 86.6% by mass or more, further preferably 86.9% by mass or more, further preferably 87.1% by mass or more, particularly preferably 87.4% by mass or more, most preferably 87.7% by mass or more, preferably 90.9% by mass or less, more preferably 90.6% by mass or less, further preferably 90.5% by mass or less, further preferably 89.6% by mass or less, particularly preferably 89.3% by mass or less, and most preferably 89.0% by mass or less. In addition, the content of the TFE unit can be selected so that the total content of the HFP unit, the FAVE unit, the TFE unit and the other monomer units is 100% by mass.
[0027] As long as the fluorinated copolymer of the present invention contains the above three kinds of monomer units, it may be a copolymer containing only the above three kinds of monomer units or a copolymer containing the above three kinds of monomer units and other monomer units.
[0028] The other monomer is not particularly limited as long as it is a monomer copolymerizable with TFE, HFP and FAVE, and may be a fluorine-containing monomer or a non-fluorine-containing monomer.
[0029] The fluorine-containing monomer is preferably selected from the group consisting of chlorotrifluoroethylene, vinyl fluoride, vinylidene fluoride, trifluoroethylene, hexafluoroisobutylene, CH2=CZ 1 (CF2) n Z 2 (Where Z 1 H or F, Z 2 is H, F or Cl, n is an integer from 1 to 10), CF2=CF-O-CH2-Rf 2 (Where Rf 2 At least one selected from the group consisting of an alkyl perfluorovinyl ether derivative represented by a perfluoroalkyl group having 1 to 5 carbon atoms, perfluoro-2,2-dimethyl-1,3-dioxole [PDD], and perfluoro-2-methylene-4-methyl-1,3-dioxolane [PMD].
[0030] As CH2=CZ 1 (CF2) n Z 2 The monomers shown include CH2=CFCF3, CH2=CH-C4F9, CH2=CH-C6F 13 , CH2=CF-C3F6H, etc.
[0031] As non-fluorine-containing monomers, hydrocarbon monomers that can be copolymerized with TFE, HFP and FAVE can be cited. As hydrocarbon monomers, for example, olefins such as ethylene, propylene, butylene, and isobutylene can be cited; alkyl vinyl ethers such as ethyl vinyl ether, propyl vinyl ether, butyl vinyl ether, isobutyl vinyl ether, and cyclohexyl vinyl ether can be cited; vinyl acetate, vinyl propionate, vinyl n-butyrate, vinyl isobutyrate, vinyl valerate, vinyl pivalate, vinyl hexanoate, vinyl octanoate, vinyl decanoate, vinyl versatate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl benzoate, vinyl p-tert-butylbenzoate, vinyl cyclohexanecarboxylate, vinyl monochloroacetate , vinyl adipate, vinyl acrylate, vinyl methacrylate, vinyl crotonate, vinyl sorbate, vinyl cinnamate, vinyl undecylenate, vinyl hydroxyacetate, vinyl hydroxypropionate, vinyl hydroxybutyrate, vinyl hydroxyvalerate, vinyl hydroxyisobutyrate, vinyl hydroxycyclohexanecarboxylate and other vinyl esters; alkyl allyl ethers such as ethyl allyl ether, propyl allyl ether, butyl allyl ether, isobutyl allyl ether, cyclohexyl allyl ether; alkyl allyl esters such as ethyl allyl ester, propyl allyl ester, butyl allyl ester, isobutyl allyl ester, cyclohexyl allyl ester, etc.
[0032] As a non-fluorine-containing monomer, it can also be a hydrocarbon monomer containing a functional group that can be copolymerized with TFE, HFP and FAVE. As a hydrocarbon monomer containing a functional group, for example, hydroxyalkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, and hydroxycyclohexyl vinyl ether can be cited; non-fluorine-containing monomers having a glycidyl group such as glycidyl vinyl ether and glycidyl allyl ether; non-fluorine-containing monomers having an amino group such as aminoalkyl vinyl ether and aminoalkyl allyl ether; non-fluorine-containing monomers having an amide group such as (methyl) acrylamide and hydroxymethyl acrylamide; bromine-containing olefins, iodine-containing olefins, bromine-containing vinyl ethers, iodine-containing vinyl ethers; non-fluorine-containing monomers having a nitrile group, etc.
[0033] The content of other monomer units in the fluorinated copolymer of the present invention is preferably 0 to 4.7 mass %, more preferably 2.8 mass % or less, further preferably 0.5 mass % or less, particularly preferably 0.1 mass % or less, based on the total monomer units.
[0034] The melt flow rate (MFR) of the fluorinated copolymer is 4.6 g / 10 min to 14.4 g / 10 min. The MFR of the copolymer is preferably 5.1 g / 10 min or more, more preferably 6.1 g / 10 min or more, further preferably 6.6 g / 10 min or more, further preferably 7.1 g / 10 min or more, particularly further preferably 8.8 g / 10 min or more, particularly preferably 9.0 g / 10 min or more, and most preferably 9.6 g / 10 min or more, preferably 14.2 g / 10 min or less, more preferably 14.0 g / 10 min or less, further preferably 12.9 g / 10 min or less, further preferably 12.0 g / 10 min or less, particularly further preferably 10.8 g / 10 min or less, particularly preferably 9.9 g / 10 min or less, and most preferably 9.6 g / 10 min or less. When the MFR is too low, a molded product having excellent deformation resistance to a bending load applied at 150°C and low permeability to chemical liquids such as low ammonia permeability cannot be obtained, and a beautiful injection molded product cannot be obtained by injection molding. When the MFR is too high, a molded product having excellent durability to a tensile force applied at 150°C, ozone resistance, and solvent crack resistance cannot be obtained.
[0035] In the present invention, the melt flow rate is a value obtained as the mass (g / 10 minutes) of a polymer flowing out from a die having an inner diameter of 2 mm and a length of 8 mm at 372° C. and a load of 5 kg per 10 minutes using a melt flow indexer G-01 (manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with ASTM D-1238.
[0036] The MFR can be adjusted by adjusting the type and amount of the polymerization initiator, the type and amount of the chain transfer agent, etc., used when polymerizing the monomers.
[0037] Every 10 of the fluorinated copolymer 6 The total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2 and -CH2OH with the number of main chain carbon atoms is 90 or less. The total number of these functional groups is preferably 80 or less, 70 or less, 60 or less, 50 or less, 40 or less, 30 or less, 25 or less, or less than 21. By making the total number of these functional groups within the above range, a molded body with excellent ozone resistance and low permeability to chemical liquids (low permeability to chemical liquids such as ammonia) and which is not easy to dissolve fluoride ions into chemical liquids such as hydrogen peroxide can be obtained.
[0038] Examples of carbonyl-containing terminal groups include -COF, -COOH, -COOR (R is an alkyl group), -CONH2, and -O(C=O)OR (R is an alkyl group). The type of the alkyl group (R) possessed by -COOR and -O(C=O)OR is determined by the polymerization initiator and chain transfer agent used in the manufacture of the fluorinated copolymer, and is, for example, an alkyl group having 1 to 6 carbon atoms such as -CH3.
[0039] The identification of the types of the functional groups and the measurement of the number of the functional groups can be performed using infrared spectroscopy.
[0040] The number of functional groups is specifically determined by the following method. First, the fluorinated copolymer is formed by cold pressing to produce a film with a thickness of 0.25 mm to 0.30 mm. The film is analyzed by Fourier transform infrared spectroscopy to obtain an infrared absorption spectrum of the fluorinated copolymer and a differential spectrum from a background spectrum of a fully fluorinated copolymer without functional groups. The number of functional groups in the fluorinated copolymer relative to each 1×10 6 The number of functional groups N per carbon atom.
[0041] N=I×K / t(A)
[0042] I: Absorbance
[0043] K: Correction coefficient
[0044] t: film thickness (mm)
[0045] For reference, absorption frequencies, molar absorption coefficients, and correction coefficients for some functional groups are shown in Table 1. The molar absorption coefficients were determined from FT-IR measurement data of low-molecular model compounds.
[0046] [Table 1]
[0047] Table 1
[0048]
[0049] The absorption frequencies of -CH2CF2H, -CH2COF, -CH2COOH, -CH2COOCH3, and -CH2CONH2 are several tens of kaise (cm-1) lower than those of -CF2H, -COF, free -COOH, and bound -COOH, -COOCH3, and -CONH2, respectively, as shown in the table. 1 ).
[0050] For example, the functional group number of -COF is the absorption frequency 1883 cm-1 due to -CF2COF. 1 The number of functional groups obtained from the absorption peak at 1840 cm-1 due to -CH2COF 1 The total number of functional groups found from the absorption peak at .
[0051] Alternatively, the number of -CF2H groups can be measured using a nuclear magnetic resonance apparatus at a temperature of (melting point of the polymer + 20)°C. 19In F-NMR measurement, it was determined from the peak integral value of -CF2H group.
[0052] Functional groups such as -CF2H groups are functional groups present at the main chain ends or side chain ends of the fluorinated copolymer and functional groups present in the main chain or in the side chain. These functional groups are introduced into the fluorinated copolymer, for example, by a chain transfer agent or a polymerization initiator used when manufacturing the fluorinated copolymer. For example, when an alcohol is used as a chain transfer agent or a peroxide having a -CH2OH structure is used as a polymerization initiator, -CH2OH is introduced into the main chain ends of the fluorinated copolymer. In addition, by polymerizing a monomer having a functional group, the above-mentioned functional group is introduced into the side chain ends of the fluorinated copolymer.
[0053] By subjecting the fluorinated copolymer having such functional groups to a wet heat treatment, a fluorination treatment, or the like, a fluorinated copolymer having the number of functional groups within the above range can be obtained. The fluorinated copolymer of the present invention is preferably subjected to a wet heat treatment or a fluorination treatment, and more preferably to a fluorination treatment. The fluorinated copolymer of the present invention also preferably has a -CF3 terminal group.
[0054] The melting point of the fluorinated copolymer is preferably 220° C. to 290° C., more preferably 250° C. to 265° C. By setting the melting point within the above range, a more beautiful injection molded product can be obtained by injection molding, and a molded product with better transparency, deformation resistance to a bending load applied at 150° C., deformation resistance to a compressive load applied at 70° C., durability to a tensile force applied at 150° C., ozone resistance, solvent crack resistance, low permeability to a chemical solution, and less elution of fluoride ions into a chemical solution can be obtained.
[0055] In the present invention, the melting point can be measured using a differential scanning calorimeter [DSC].
[0056] The haze value of the fluorinated copolymer of the present invention is preferably 14.0% or less, more preferably 13.0% or less. When the haze value is within the above range, when a molded body such as a pipe, a joint, a flow meter body, a bottle, a nut, etc. is obtained using the fluorinated copolymer of the present invention, it is easy to observe the inside of the molded body visually or with a camera, and it is easy to confirm the flow rate and the remainder of the contents. The haze value can be reduced by adjusting the content of the HFP unit and the FAVE unit of the fluorinated copolymer and the melt flow rate (MFR).
[0057] In the present invention, the haze value can be measured in accordance with JIS K 7136.
[0058] The amount of fluorine ions eluted from the fluorinated copolymer of the present invention detected in an immersion test in hydrogen peroxide water is preferably 4.0 ppm or less, more preferably 2.8 ppm or less, on a mass basis.
[0059] In the present invention, the immersion test in hydrogen peroxide can be carried out as follows: a test piece having a weight equivalent to 10 molded bodies (15 mm × 15 mm × 0.2 mm) is prepared using a fluorinated copolymer, and a polypropylene bottle containing the test piece and 15 g of a 3% by mass hydrogen peroxide solution is placed in a constant temperature bath at 95°C for 20 hours.
[0060] The ammonia permeability of the copolymer is preferably 600 mg·cm / m 2 The copolymer of the present invention has excellent low ammonia permeability due to the appropriate adjustment of the content of HFP units and FAVE units, melt flow rate (MFR) and number of functional groups. That is, by using the copolymer of the present invention, a molded body that is difficult for ammonia solution and the like to permeate can be obtained.
[0061] In the present invention, the ammonia water permeability can be measured under the conditions of a temperature of 37° C. and 27 days. The ammonia water permeability can be specifically measured by the method described in the Examples.
[0062] The fluorinated copolymer of the present invention can also be produced by any polymerization method such as bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc. In these polymerization methods, various conditions such as temperature and pressure, polymerization initiator, chain transfer agent, solvent, and other additives can be appropriately set according to the desired composition and amount of the fluorinated copolymer.
[0063] As the polymerization initiator, an oil-soluble radical polymerization initiator or a water-soluble radical initiator can be used.
[0064] The oil-soluble radical polymerization initiator may be a known oil-soluble peroxide, and the following may be cited as representative examples:
[0065] Dialkyl peroxycarbonates such as di-n-propyl peroxydicarbonate, di-isopropyl peroxydicarbonate and di-sec-butyl peroxydicarbonate;
[0066] Peroxyesters such as tert-butyl peroxyisobutyrate and tert-butyl peroxypivalate;
[0067] Dialkyl peroxides such as di-tert-butyl peroxide;
[0068] Di[fluoro(or chlorofluoro)acyl]peroxides; etc.
[0069] Examples of the di[fluoro(or fluorochloro)acyl]peroxides include diacyl peroxides represented by [(RfCOO)-]2 (Rf is a perfluoroalkyl group, an ω-hydroperfluoroalkyl group or a fluorochloroalkyl group).
[0070] Examples of the di[fluoro(or chlorofluoro)acyl]peroxides include di(ω-hydroperfluorohexanoyl)peroxide, di(ω-hydro-dodecafluoroheptanoyl)peroxide, di(ω-hydro-tetrafluorooctanoyl)peroxide, di(ω-hydro-hexafluorononanoyl)peroxide, di(perfluorobutyryl)peroxide, di(perfluorovaleranoyl)peroxide, di(perfluorohexanoyl)peroxide, di(perfluoroheptanoyl)peroxide, di(perfluorooctanoyl)peroxide, di(perfluorononanoyl)peroxide, and di(ω-chloro-hexafluorobutyryl)peroxide. , di(ω-chloro-decafluorohexanoyl)peroxide, di(ω-chloro-tetrafluorooctanoyl)peroxide, ω-hydro-dodecafluoroheptanoyl-ω-hydrohexafluorononanoyl-peroxide, ω-chloro-hexafluorobutyryl-ω-chloro-decafluorohexanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-peroxide, ω-hydro-dodecafluoroheptanoyl-perfluorobutyryl-peroxide, di(dichloropentafluorobutyryl)peroxide, di(trichlorooctafluorohexanoyl)peroxide, di(tetrachloroundecanoyl)peroxide, di(pentachlorotetrafluorodecanoyl)peroxide, di(undecachlorotriacontanoyl)peroxide, and the like.
[0071] As the water-soluble free radical polymerization initiator, it can be a known water-soluble peroxide, for example, ammonium salts, potassium salts, sodium salts of persulfuric acid, perboric acid, perchloric acid, perphosphoric acid, percarbonic acid, etc., tert-butyl peroxymaleate, tert-butyl hydroperoxide, etc. It can also contain a reducing agent such as sulfites, and its amount can be 0.1 to 20 times that of the peroxide.
[0072] If an oil-soluble free radical polymerization initiator is used as a polymerization initiator, the generation of -COF and -COOH can be avoided, and the total number of -COF and -COOH of the fluorinated copolymer can be easily adjusted to the above range, so it is preferred. In addition, if an oil-soluble free radical polymerization initiator is used, it is also easy to adjust the total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2 and -CH2OH to the above range. In particular, it is preferred to manufacture the fluorinated copolymer by suspension polymerization using an oil-soluble free radical polymerization initiator. As an oil-soluble free radical polymerization initiator, it is preferred to select at least one of the groups consisting of dialkyl peroxycarbonates and di[fluorine (or chlorofluoride) acyl] peroxides, and more preferably at least one of the groups consisting of di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate and di(ω-hydrogen-dodecanoyl) peroxide.
[0073] Examples of chain transfer agents include hydrocarbons such as ethane, isopentane, n-hexane, and cyclohexane; aromatics such as toluene and xylene; ketones such as acetone; acetates such as ethyl acetate and butyl acetate; alcohols such as methanol, ethanol, and 2,2,2-trifluoroethanol; mercaptans such as methyl mercaptan; halogenated hydrocarbons such as carbon tetrachloride, chloroform, dichloromethane, and chloromethane; 3-fluorobenzotrifluoride, etc. The amount added can vary depending on the chain transfer constant of the compound used, and is usually used in the range of 0.01 to 20 parts by mass relative to 100 parts by mass of the solvent.
[0074] For example, when dialkyl peroxycarbonates, di[fluoro(or chlorofluoro)acyl]peroxides, etc. are used as polymerization initiators, the molecular weight of the obtained fluorinated copolymer becomes too high, and it is sometimes difficult to adjust the desired melt flow rate, but a chain transfer agent can be used to adjust the molecular weight. It is particularly preferred to manufacture the fluorinated copolymer by suspension polymerization using a chain transfer agent such as alcohols and an oil-soluble free radical polymerization initiator.
[0075] Examples of the solvent include water, a mixed solvent of water and alcohol, etc. Alternatively, the monomer used for polymerization of the fluorinated copolymer of the present invention may be used as the solvent.
[0076] In suspension polymerization, in addition to water, fluorine-based solvents can also be used. As fluorine-based solvents, hydrochlorofluoroalkanes such as CH3CClF2, CH3CCl2F, CF3CF2CCl2H, CF2ClCF2CFHCl, etc.; chlorofluoroalkanes such as CF2ClCFClCF2CF3, CF3CFClCFClCF3, etc.; perfluorocyclobutane, CF3CF2CF2CF3, CF3CF2CF2CF2CF3, CF3CF2CF2CF2CF2CF3, etc. perfluoroalkanes, etc., among which perfluoroalkanes are preferred. From the aspects of suspensibility and economy, the amount of fluorine-based solvent used is preferably 10 to 100 parts by mass relative to 100 parts by mass of the solvent.
[0077] The polymerization temperature is not particularly limited and may be 0° C. to 100° C. In addition, when the decomposition rate of the polymerization initiator is too fast, such as when dialkyl peroxycarbonates, di[fluoro(or chlorofluoro)acyl]peroxides, etc. are used as the polymerization initiator, it is preferred to adopt a relatively low polymerization temperature such as a range of 0° C. to 35° C.
[0078] The polymerization pressure is appropriately determined according to other polymerization conditions such as the type of solvent used, the amount of solvent, the vapor pressure, the polymerization temperature, etc., and can generally be 0 MPaG to 9.8 MPaG. The polymerization pressure is preferably 0.1 MPaG to 5 MPaG, more preferably 0.5 MPaG to 2 MPaG, and further preferably 0.5 MPaG to 1.5 MPaG. In addition, when the polymerization pressure is 1.5 MPaG or more, the production efficiency can be improved.
[0079] As the additive in the polymerization, for example, a suspension stabilizer can be cited. As a suspension stabilizer, as long as it is an existing known suspension stabilizer, there is no particular limitation, and methylcellulose, polyvinyl alcohol, etc. can be used. If a suspension stabilizer is used, the suspended particles generated by the polymerization reaction are stably dispersed in the aqueous medium, so even if a reaction tank made of SUS that is not subjected to anti-adhesion treatments such as glass lining is used, the suspended particles are not easily attached to the reaction tank. Therefore, a reaction tank that withstands high pressure can be used, so polymerization under high pressure can be carried out, and production efficiency can be improved. In contrast, when polymerization is carried out without using a suspension stabilizer, if a reaction tank made of SUS that is not subjected to anti-adhesion treatment is used, the suspended particles are likely to adhere and reduce production efficiency. The concentration of the suspension stabilizer relative to the aqueous medium can be appropriately adjusted according to the conditions.
[0080] In the case of obtaining an aqueous dispersion containing a fluoropolymer by polymerization, the dry fluoropolymer can be recovered by precipitating, cleaning, and drying the fluoropolymer contained in the aqueous dispersion. In addition, in the case of obtaining a fluoropolymer in the form of a slurry by polymerization, the dry fluoropolymer can be recovered by taking out the slurry from the reaction vessel and cleaning and drying. By drying, the fluoropolymer can be recovered in the form of a powder.
[0081] The fluorinated copolymer obtained by polymerization can be formed into pellets. There is no particular limitation on the molding method for forming the pellets, and a conventionally known method can be used. For example, there can be cited a method in which the fluorinated copolymer is melt-extruded using a single-screw extruder, a twin-screw extruder, or a tandem extruder, and the fluorinated copolymer is cut into a predetermined length to form a pellet. The extrusion temperature during melt extrusion needs to be changed according to the melt viscosity and the manufacturing method of the fluorinated copolymer, and is preferably the melting point of the fluorinated copolymer + 20°C to the melting point of the fluorinated copolymer + 140°C. There is no particular limitation on the cutting method of the fluorinated copolymer, and conventionally known methods such as a wire cutting method, a heat cutting method, an underwater cutting method, and a sheet cutting method can be used. The volatile components in the pellets can also be removed by heating the obtained pellets (degassing treatment). The obtained pellets can also be treated by contacting with warm water at 30°C to 200°C, steam at 100°C to 200°C, or hot air at 40°C to 200°C.
[0082] The fluorinated copolymer obtained by polymerization can also be heated to a temperature of 100°C or above in the presence of air and water (wet heat treatment). As a method for wet heat treatment, for example, the following method can be cited: using an extruder, while supplying air and water, the fluorinated copolymer obtained by polymerization is melted and extruded. By wet heat treatment, the thermally unstable functional groups such as -COF and -COOH of the fluorinated copolymer can be converted into thermally more stable -CF2H, and the total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2 and -CH2OH of the fluorinated copolymer can be easily adjusted to the above range. In addition to air and water, the conversion reaction to -CF2H can be promoted by heating the fluorinated copolymer in the presence of an alkali metal salt. However, it should be noted that, depending on the use of the fluorinated copolymer, contamination caused by alkali metal salts should be avoided.
[0083] The fluorinated copolymer obtained by polymerization can be subjected to fluorination treatment. From the aspect of obtaining a molded body that makes it difficult for fluoride ions to dissolve into a liquid such as hydrogen peroxide, it is preferred to subject the fluorinated copolymer to fluorination treatment. The fluorination treatment can be carried out by contacting the fluorinated copolymer that has not been fluorinated with a fluorinated compound. Through the fluorination treatment, thermally unstable functional groups such as -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2, and thermally relatively stable functional groups such as -CF2H of the fluorinated copolymer can be converted into thermally extremely stable -CF3. As a result, the total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2 and -CH2OH of the fluorinated copolymer can be easily adjusted to the above range.
[0084] The fluorine-containing compound is not particularly limited, and a fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. As the above-mentioned fluorine radical source, F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, fluorinated halogens (such as IF5, ClF3), etc. can be cited.
[0085] The fluorine free radical source such as F2 gas can be 100% concentration, but from the aspect of safety, it is preferably mixed with an inert gas and diluted to 5% to 50% by mass for use, and more preferably diluted to 15% to 30% by mass for use. As the above-mentioned inert gas, nitrogen, helium, argon, etc. can be cited, and nitrogen is preferred from the aspect of economy.
[0086] The conditions of the fluorination treatment are not particularly limited, and the fluorinated copolymer in a molten state may be brought into contact with the fluorinated compound, but it may be generally carried out at a temperature below the melting point of the fluorinated copolymer, preferably at 20°C to 220°C, and more preferably at 100°C to 200°C. The above-mentioned fluorination treatment is generally carried out for 1 hour to 30 hours, preferably for 5 hours to 25 hours. The fluorination treatment is preferably a treatment in which the fluorinated copolymer that has not been fluorinated is brought into contact with fluorine gas (F2 gas).
[0087] The fluorinated copolymer of the present invention may be mixed with other components as required to obtain a composition. Other components include fillers, plasticizers, processing aids, mold release agents, pigments, flame retardants, lubricants, light stabilizers, weather stabilizers, conductive agents, antistatic agents, ultraviolet absorbers, antioxidants, foaming agents, fragrances, oils, softeners, dehydrofluorination agents, etc.
[0088] As fillers, for example, silicon dioxide, kaolin, clay, organic clay, talc, mica, aluminum oxide, calcium carbonate, calcium terephthalate, titanium oxide, calcium phosphate, calcium fluoride, lithium fluoride, cross-linked polystyrene, potassium titanate, carbon, boron nitride, carbon nanotubes, glass fibers, etc. can be cited. As conductive agents, carbon black, etc. can be cited. As plasticizers, dioctyl phthalate, pentaerythritol, etc. can be cited. As processing aids, carnauba wax, sulfone compounds, low molecular weight polyethylene, fluorine-based additives, etc. can be cited. As dehydrofluorination agents, organic onium, amidines, etc. can be cited.
[0089] As the other components, other polymers other than the above-mentioned fluorinated copolymers may be used. Examples of the other polymers include fluorinated resins other than the above-mentioned fluorinated copolymers, fluorinated rubbers, and non-fluorinated polymers.
[0090] Examples of the method for producing the composition include a method of dry-mixing the fluorinated copolymer and other components; a method of preliminarily mixing the fluorinated copolymer and other components in a mixer and then melt-kneading them in a kneader, melt extruder or the like; and the like.
[0091] The fluorinated copolymer of the present invention or the above-mentioned composition can be used as a processing aid, a molding material, etc., and is preferably used as a molding material. In addition, the aqueous dispersion, solution, suspension, and copolymer / solvent system of the fluorinated copolymer of the present invention can also be used, and they can be applied as a coating, or used for encapsulation, impregnation, and film casting. However, the fluorinated copolymer of the present invention is preferably used as the above-mentioned molding material because it has the above-mentioned characteristics.
[0092] The fluorinated copolymer of the present invention or the above composition may be molded to obtain a molded product.
[0093] The method for molding the above-mentioned fluorinated copolymer or the above-mentioned composition is not particularly limited, and injection molding, extrusion molding, compression molding, blow molding, transfer molding, rotational molding, roll lining molding, etc. can be cited. As a molding method, among them, preferably extrusion molding, compression molding, injection molding or transfer molding, from the aspect of being able to produce a molded body with high productivity, more preferably injection molding, extrusion molding or transfer molding, further preferably injection molding. That is, as a molded body, preferably an extrusion molded body, a compression molded body, an injection molded body or a transfer molded body, from the aspect of being able to produce with high productivity, more preferably an injection molded body, an extrusion molded body or a transfer molded body, further preferably an injection molded body. By molding the fluorinated copolymer of the present invention by injection molding, a beautiful molded product can be obtained.
[0094] Examples of the molded article containing the fluorinated copolymer of the present invention include nuts, bolts, joints, films, bottles, washers, wire coatings, tubes, hoses, pipes, valves, sheets, seals, gaskets, tanks, rollers, containers, cocks, connectors, filter cases, filter covers, flow meters, pumps, wafer carriers, wafer cassettes, and the like.
[0095] The fluorinated copolymer, the above composition or the above molded article of the present invention can be used for the following purposes, for example.
[0096] Films for food packaging, lining materials for fluid delivery pipelines used in food manufacturing processes, gaskets, sealing materials, sheets and other fluid delivery components for food manufacturing equipment;
[0097] Chemical plugs, packaging films, lining materials, gaskets, sealing materials, thin plates and other reagent delivery components for fluid delivery pipelines used in chemical manufacturing processes;
[0098] Lining components for the inner surface of liquid tanks and piping in chemical equipment and semiconductor factories;
[0099] O (square) rings / tubes / gaskets, valve core materials, hoses, sealing materials, etc. used in automobile fuel systems and peripheral devices; fuel delivery components such as hoses and sealing materials used in automobile AT devices;
[0100] Flange gaskets, shaft seals, valve stem seals, sealing materials, hoses, etc. used in car engines and peripheral devices of automobiles; other automobile components such as automobile brake hoses, air conditioning hoses, radiator hoses, wire covering materials, etc.;
[0101] Semiconductor manufacturing equipment O (square) rings, tubes, gaskets, valve core materials, hoses, sealing materials, rollers, gaskets, diaphragms, joints and other semiconductor device liquid delivery components;
[0102] Coating rollers, hoses, tubes, ink containers and other coating and ink components for coating equipment;
[0103] Food and beverage conveying components such as tubes or hoses for food and beverages, tubes, hoses, belts, gaskets, joints, etc., food packaging materials, and glass cooking equipment;
[0104] Waste liquid transmission components such as pipes and hoses used for waste liquid transmission;
[0105] Components for high-temperature liquid transmission such as pipes and hoses used for high-temperature liquid transmission;
[0106] Steam piping components such as pipes and hoses used for steam piping;
[0107] Pipe corrosion protection tapes such as tapes wrapped around pipes on ship decks, etc.;
[0108] Various covering materials such as wire covering materials, optical fiber covering materials, transparent surface covering materials and back-side agents provided on the light incident side surface of photovoltaic elements of solar cells;
[0109] Diaphragms of diaphragm pumps and sliding components such as various sealing gaskets;
[0110] Weather-resistant covers for agricultural films, various roofing materials, sidewalls, etc.;
[0111] Interior materials used in the construction field, non-combustible fireproof safety glass and other glass covering materials;
[0112] Lining materials for laminated steel sheets used in the home appliance field, etc.
[0113] Further examples of the fuel delivery member used in the fuel system of the above-mentioned automobile include fuel hoses, filler hoses, evaporator hoses, etc. The above-mentioned fuel delivery member can also be used as a fuel delivery member for sour gasoline, alcohol fuel, and fuel added with gasoline additives such as methyl tert-butyl ether resistance and amine resistance.
[0114] The chemical plug and packaging film have excellent chemical resistance to acids, etc. In addition, as the chemical liquid conveying member, an anti-corrosion tape wound around the chemical equipment piping can also be cited.
[0115] Examples of the molded article include automobile radiator water chambers, chemical tanks, bellows, partitions, rollers, gasoline tanks, waste liquid transport containers, high temperature liquid transport containers, fisheries and fish farming tanks, and the like.
[0116] Examples of the molded bodies include automobile bumpers, door trims, instrument panels, food processing equipment, cooking machines, waterproof and oil-proof glass, lighting-related instruments, indicator panels and housings of OA instruments, electrically illuminated signboards, display screens, liquid crystal display screens, mobile phones, printer chassis, electrical and electronic components, groceries, trash cans, bathtubs, integrated bathrooms, ventilation fans, lighting frames, and the like.
[0117] The molded article containing the fluorinated copolymer of the present invention is excellent in transparency, deformation resistance to a bending load applied at 150°C, deformation resistance to a compressive load applied at 70°C, durability to a tensile force applied at 150°C, ozone resistance, solvent crack resistance, and low permeability to chemical liquids, and can therefore be suitably used for valves, joints, nuts, flow meters, piping components, pipes, films, wire coverings, and the like.
[0118] The molded article containing the fluorinated copolymer of the present invention can be suitably used as a compressed member such as a gasket or a sealing gasket. The compressed member of the present invention may be a gasket or a sealing gasket.
[0119] The size and shape of the compressed member of the present invention can be appropriately set according to the purpose, and there is no particular limitation. The shape of the compressed member of the present invention can be, for example, annular. In addition, the compressed member of the present invention can have a circular, elliptical, quadrilateral with rounded corners, etc. shape when viewed from above, and has a through hole in its central portion.
[0120] The compressed member of the present invention is preferably used as a member for constituting a non-aqueous electrolyte battery. The compressed member of the present invention is particularly suitable as a member used in a state of contact with a non-aqueous electrolyte in a non-aqueous electrolyte battery. That is, the compressed member of the present invention may have a liquid contact surface with the non-aqueous electrolyte in the non-aqueous electrolyte battery.
[0121] The nonaqueous electrolyte battery is not particularly limited as long as it is a battery having a nonaqueous electrolyte, and examples thereof include lithium ion secondary batteries, lithium ion capacitors, etc. In addition, members constituting the nonaqueous electrolyte battery include sealing members, insulating members, and the like.
[0122] The non-aqueous electrolyte is not particularly limited, and one or more of known solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, etc. can be used. The non-aqueous electrolyte battery can further include an electrolyte. The electrolyte is not particularly limited, and LiClO4, LiAsF6, LiPF6, LiBF4, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc. can be used.
[0123] The compressed member of the present invention can be preferably used as a sealing member such as a sealing gasket or a sealing pad, or an insulating member such as an insulating gasket or an insulating pad. A sealing member is a member used to prevent leakage of liquid or gas or intrusion of liquid or gas from the outside. An insulating member is a member used for electrical insulation. The compressed member of the present invention can also be a member used for both sealing and insulation purposes.
[0124] The compressed member of the present invention can be suitably used as a sealing member for a non-aqueous electrolyte battery or an insulating member for a non-aqueous electrolyte battery. In addition, the compressed member of the present invention has excellent insulating properties because it contains the above-mentioned fluorinated copolymer. Therefore, when the compressed member of the present invention is used as an insulating member, it is firmly attached to two or more conductive members to prevent short circuits for a long time.
[0125] The fluorinated copolymer of the present invention can be suitably used as a material for forming an electric wire coating. A coated electric wire having a coating layer containing the fluorinated copolymer of the present invention has almost no fluctuation in outer diameter and is therefore excellent in electrical properties.
[0126] The covered electric wire comprises a core wire and a covering layer disposed around the core wire and containing the fluorinated copolymer of the present invention. For example, an extruded body formed by melt-extruding the fluorinated copolymer of the present invention on the core wire can be used as the covering layer. The covered electric wire is suitable for LAN cables (Ethernet Cables), high-frequency transmission cables, flat cables, heat-resistant cables, etc., and is suitable for transmission cables such as LAN cables (Ethernet Cables) and high-frequency transmission cables.
[0127] As the material of the core wire, a metal conductor material such as copper or aluminum can be used. The core wire preferably has a diameter of 0.02 mm to 3 mm. The core wire diameter is more preferably 0.04 mm or more, further preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. The core wire diameter is more preferably 2 mm or less.
[0128] As specific examples of the core wire, AWG (American Wire Gauge)-46 (solid copper wire with a diameter of 40 μm), AWG-26 (solid copper wire with a diameter of 404 μm), AWG-24 (solid copper wire with a diameter of 510 μm), AWG-22 (solid copper wire with a diameter of 635 μm), etc. can be used.
[0129] The thickness of the coating layer is preferably 0.1 mm to 3.0 mm, and the thickness of the coating layer is also preferably 2.0 mm or less.
[0130] As a high-frequency transmission cable, a coaxial cable can be cited. A coaxial cable generally has a structure in which an inner conductor, an insulating coating, an outer conductor layer and a protective coating are sequentially stacked from the core to the periphery. The molded body containing the fluorinated copolymer of the present invention can be suitably used as an insulating coating containing a fluorinated copolymer. The thickness of each layer in the above structure is not particularly limited. Generally, the diameter of the inner conductor is about 0.1 mm to 3 mm, the thickness of the insulating coating is about 0.3 mm to 3 mm, the thickness of the outer conductor layer is about 0.5 mm to 10 mm, and the thickness of the protective coating is about 0.5 mm to 2 mm.
[0131] The coating layer may contain air bubbles, and the air bubbles are preferably uniformly distributed in the coating layer.
[0132] The average bubble diameter of the bubbles is not limited, and is, for example, preferably 60 μm or less, more preferably 45 μm or less, further preferably 35 μm or less, further preferably 30 μm or less, particularly preferably 25 μm or less, and particularly preferably 23 μm or less. In addition, the average bubble diameter is preferably 0.1 μm or more, more preferably 1 μm or more. The average bubble diameter can be obtained by obtaining an electron microscope image of a cross section of the wire, calculating the diameter of each bubble by image processing, and averaging them.
[0133] The foaming rate of the coating layer may be 20% or more. More preferably, it is 30% or more, further preferably, it is 33% or more, and further preferably, it is 35% or more. The upper limit is not particularly limited, for example, it is 80%. The upper limit of the foaming rate may be 60%. The foaming rate is a value calculated as ((specific gravity of the wire coating material - specific gravity of the coating layer) / specific gravity of the wire coating material) × 100. The foaming rate can be appropriately adjusted according to the application by, for example, adjusting the amount of gas inserted in the extruder described later, or by selecting the type of dissolved gas.
[0134] The covered electric wire may also have other layers between the core wire and the covering layer, and may further have other layers (outer layers) around the covering layer. When the covering layer contains bubbles, the electric wire of the present invention may also be a two-layer structure (skin-foam) in which a non-foam layer is inserted between the core wire and the covering layer; a two-layer structure (foam-skin) in which a non-foam layer is covered on the outer layer; and a three-layer structure (skin-foam-skin) in which a non-foam layer is covered on the outer layer of the skin-foam. The non-foam layer is not particularly limited, and may be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyolefin resins such as polyethylene [PE], and polyvinyl chloride [PVC].
[0135] The covered electric wire can be produced, for example, by heating a fluorinated copolymer using an extruder and extruding the fluorinated copolymer in a molten state onto a core wire to form a covering layer.
[0136] When forming the coating, it is also possible to heat the fluorinated copolymer, under the molten state of the fluorinated copolymer, introduce gas into the fluorinated copolymer, thereby forming the above-mentioned coating containing bubbles. As the gas, for example, a mixture of gases such as difluorochloromethane, nitrogen, carbon dioxide or the above-mentioned gases can be used. The gas can be introduced into the heated fluorinated copolymer in the form of pressurized gas, or it can be produced by mixing a chemical foaming agent in the fluorinated copolymer. The gas dissolves in the molten state of the fluorinated copolymer.
[0137] Furthermore, the fluorinated copolymer of the present invention can be suitably used as a material for products for high-frequency signal transmission.
[0138] The high-frequency signal transmission product is not particularly limited as long as it is a product used for the transmission of high-frequency signals, and examples thereof include (1) insulating plates of high-frequency circuits, insulating materials of connecting components, molded plates such as printed wiring boards, (2) molded bodies such as bases and antenna covers of high-frequency vacuum tubes, and (3) coated wires such as coaxial cables and LAN cables. The high-frequency signal transmission product can be suitably used in equipment that utilizes microwaves, particularly 3 GHz to 30 GHz microwaves, such as satellite communication equipment and mobile phone base stations.
[0139] In the above-mentioned products for high-frequency signal transmission, the fluorinated copolymer of the present invention can be suitably used as an insulator since it has a low dielectric loss tangent.
[0140] As the above-mentioned (1) molded plate, a printed wiring board is preferred from the aspect of obtaining good electrical characteristics. The above-mentioned printed wiring board is not particularly limited, and examples thereof include printed wiring boards of electronic circuits such as mobile phones, various computers, and communication equipment. As the above-mentioned (2) molded body, a radome is preferred from the aspect of low dielectric loss.
[0141] The fluorinated copolymer of the present invention can be suitably used for a film.
[0142] The film of the present invention is useful as a release film. The release film can be produced by molding the fluorinated copolymer of the present invention by melt extrusion molding, calendaring molding, compression molding, cast molding, etc. From the perspective of obtaining a uniform film, the release film can be produced by melt extrusion molding.
[0143] The film of the present invention can be applied to the surface of a roller used in OA equipment. In addition, the fluorinated copolymer of the present invention can be formed into a necessary shape by extrusion molding, compression molding, press molding, etc., and formed into a sheet, film, or tube, and used as a surface material for OA equipment rollers or OA equipment belts, etc. In particular, thin-walled tubes and films can be produced by melt extrusion molding.
[0144] The fluorinated copolymer of the present invention can also be suitably used in tubes, bottles and the like.
[0145] Although the embodiments have been described above, it should be understood that various modifications may be made to the embodiments and details without departing from the spirit and scope of the claims.
[0146] <1> According to a first aspect of the present invention, there is provided a fluorinated copolymer comprising a tetrafluoroethylene unit, a hexafluoropropylene unit and a fluoro(alkyl vinyl ether) unit, wherein:
[0147] The content of the hexafluoropropylene unit is 8.6% to 11.9% by mass based on the total monomer units.
[0148] The content of the fluoro(alkyl vinyl ether) unit is 0.5% by mass to 1.9% by mass based on the total monomer units.
[0149] The melt flow rate at 372°C is 4.6 g / 10 min to 14.4 g / 10 min.
[0150] The total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2 and -CH2OH is relative to every 10 6 The number of carbon atoms in the main chain is less than 90.
[0151] <2> According to a second aspect of the present invention, there is provided a fluorinated copolymer according to the first aspect, wherein the content of the hexafluoropropylene unit is 9.1% by mass to 11.0% by mass based on the total monomer units.
[0152] <3> According to a third aspect of the present invention, there is provided the fluorinated copolymer according to the first aspect or the second aspect, wherein the content of the fluorinated (alkyl vinyl ether) unit is 0.5 to 1.3 mass % based on all monomer units.
[0153] <4> According to a fourth aspect of the present invention, there is provided a fluorinated copolymer according to any one of the first to third aspects, wherein the melt flow rate at 372° C. is from 5.1 g / 10 min to 14.0 g / 10 min.
[0154] <5> According to a fifth aspect of the present invention, there is provided a fluorinated copolymer according to any one of the first to fourth aspects, wherein the fluorinated (alkyl vinyl ether) unit is a perfluoro (propyl vinyl ether) unit.
[0155] <6> According to a sixth aspect of the present invention, there is provided an injection-molded article comprising the fluorinated copolymer according to any one of the first to fifth aspects.
[0156] <7> According to a seventh aspect of the present invention, there is provided a covered electric wire comprising a covering layer containing the fluorinated copolymer according to any one of the first to fifth aspects.
[0157] <8> According to an eighth aspect of the present invention, there is provided a molded article comprising the fluorinated copolymer according to any one of the first to fifth aspects, wherein the molded article is a valve, a joint, a nut, a flow meter, a pipe, a membrane or a wire coating.
[0158] Example
[0159] Next, embodiments of the present invention will be described with reference to examples, but the present invention is not limited to the examples.
[0160] Each numerical value in the examples was measured by the following method.
[0161] (Content of monomer units)
[0162] The content of each monomer unit of the fluorinated copolymer is measured using an NMR analyzer (for example, AVANCE300 high temperature probe manufactured by Bruker BioSpin) or an infrared absorption analyzer (Spectrum One manufactured by Perkin Elmer).
[0163] (Melt Flow Rate (MFR))
[0164] The MFR of the fluorinated copolymer was determined by measuring the mass (g / 10 minutes) of the polymer flowing out from a die having an inner diameter of 2 mm and a length of 8 mm at 372°C and a load of 5 kg using a melt flow indexer G-01 (manufactured by Toyo Seiki Seisaku-sho, Ltd.) in accordance with ASTM D-1238.
[0165] (Amount of -CF2H)
[0166] The number of -CF2H groups in the fluorinated copolymer was measured using a nuclear magnetic resonance apparatus AVANCE-300 (manufactured by Bruker BioSpin) at a temperature of (melting point of the polymer + 20)°C. 19 In F-NMR measurement, it was determined from the peak integral value of -CF2H group.
[0167] (Amount of -COOH, -COOCH3, -CH2OH, -COF, -CF=CF2, -CONH2)
[0168] The dry powder or pellets obtained in the examples and comparative examples are formed by cold pressing to produce films with a thickness of 0.25 mm to 0.3 mm. The film is scanned 40 times by a Fourier transform infrared spectrometer [FT-IR (Spectrum One, manufactured by PerkinElmer)] and analyzed to obtain an infrared absorption spectrum. The obtained infrared absorption spectrum is compared with the infrared absorption spectrum of a known film to determine the type of terminal group. In addition, the absorption peak of a specific functional group that appears in the differential spectrum between the obtained infrared absorption spectrum and the infrared absorption spectrum of a known film is calculated according to the following formula (A) for every 1×10 6 The number of functional groups N per carbon atom.
[0169] N=I×K / t(A)
[0170] I: Absorbance
[0171] K: Correction coefficient
[0172] t: film thickness (mm)
[0173] For reference, the absorption frequency, molar absorption coefficient and correction coefficient of the functional groups in the examples are shown in Table 2. The molar absorption coefficient was determined from the FT-IR measurement data of the low molecular model compound.
[0174] [Table 2]
[0175] Table 2
[0176]
[0177] (-OC(=O)OR(carbonate group) number)
[0178] The analysis was performed by the method described in International Publication No. 2019 / 220850. The absorption frequency was set to 1817 cm- 1 The number of -OC(=O)OR (carbonate groups) was calculated in the same manner as the method for calculating the number of functional groups N, except that the molar absorptivity was set to 170 (l / cm / mol) and the correction factor was set to 1426.
[0179] (Melting Point)
[0180] Regarding the melting point of the fluorinated copolymer, a differential scanning calorimeter (trade name: X-DSC7000, manufactured by Hitachi High-Tech Science Co., Ltd.) was used to perform the first temperature increase from 200°C to 350°C at a temperature increase rate of 10°C / min, then cooled from 350°C to 200°C at a cooling rate of 10°C / min, and then the second temperature increase from 200°C to 350°C was performed again at a temperature increase rate of 10°C / min. The melting point was determined from the peak of the melting curve generated in the second temperature increase process.
[0181] Comparative Example 1
[0182] 40.25kg of deionized water and 0.033kg of methanol were added to an autoclave with a stirrer of a volume of 174L, and the autoclave was fully replaced with vacuum nitrogen. Then, the autoclave was vacuum degassed, 40.25kg of HFP and 0.28kg of PPVE were added to the autoclave in a vacuum state, and the autoclave was heated to 30.0°C. Next, TFE was added until the internal pressure of the autoclave reached 0.873MPa, and then 0.63kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.873MPa, and the set pressure was maintained by continuously adding TFE. 0.033kg of methanol was added 1.5 hours after the start of polymerization. 2 hours and 4 hours after the start of polymerization, 0.63 kg of DHP was added and the internal pressure was reduced by 0.001 MPa. 6 hours later, 0.48 kg was added and the internal pressure was reduced by 0.001 MPa. Then, 0.13 kg of DHP was added every 2 hours until the reaction was completed, and the internal pressure was reduced by 0.001 MPa each time.
[0183] It should be noted that 0.10 kg of PPVE was added when the continuous additional input amount of TFE reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. In addition, 0.033 kg of methanol was added to the autoclave when the additional input amount of TFE reached 6.0 kg and 18.1 kg, respectively. Then, the polymerization was terminated when the additional input amount of TFE reached 40.25 kg. After the polymerization was completed, the unreacted TFE and HFP were released to obtain a wet powder. Then, the wet powder was washed with pure water and dried at 150°C for 10 hours to obtain 47.3 kg of dry powder.
[0184] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of the copolymer. The HFP content and PPVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.
[0185] After degassing the obtained pellets at 200°C for 8 hours in an electric furnace, the pellets were placed in a vacuum vibration reactor VVD-30 (manufactured by Ohkawara Manufacturing Co., Ltd.) and the temperature was raised to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced into atmospheric pressure. 0.5 hours after the introduction of F2 gas, the gas was temporarily evacuated and F2 gas was introduced again. After a further 0.5 hours, the gas was evacuated again and F2 gas was introduced again. Then, the above-mentioned F2 gas introduction and evacuation operations were continued once for 1 hour, and the reaction was carried out at a temperature of 200°C for 8 hours. After the reaction was completed, the reactor was fully replaced with N2 gas, the fluorination reaction was terminated, and pellets were obtained. Using the obtained pellets, various physical properties were measured by the above method. The results are shown in Table 3.
[0186] Comparative Example 2
[0187] The amount of methanol added before the start of polymerization was changed to 0.048 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.048 kg, the amount of PPVE added before the start of polymerization was changed to 0.36 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.11 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.906 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The obtained pellets were used to measure the HFP content and PPVE content by the above method. The results are shown in Table 3.
[0188] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. Using the obtained pellets, various physical properties were measured by the above-mentioned methods. The results are shown in Table 3.
[0189] Comparative Example 3
[0190] 40.25 kg of deionized water and 0.333 kg of methanol were added to an autoclave with a stirrer of a volume of 174 L, and the autoclave was fully replaced with vacuum nitrogen. Then, the autoclave was vacuum degassed, 40.25 kg of HFP and 0.64 kg of PPVE were added to the autoclave in a vacuum state, and the autoclave was heated to 25.5 ° C. Next, TFE was added until the internal pressure of the autoclave reached 0.872 MPa, and then 1.25 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.872 MPa, and the set pressure was maintained by continuously adding TFE. 0.333 kg of methanol was added 1.5 hours after the start of polymerization. 1.25 kg of DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was reduced by 0.002 MPa. 0.96 kg was added 6 hours later, and the internal pressure was reduced by 0.002 MPa. Then, 0.25 kg of DHP was added every 2 hours until the reaction was completed, and the internal pressure was reduced by 0.002 MPa each time.
[0191] It should be noted that 0.14 kg of PPVE was added when the continuous additional input amount of TFE reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. In addition, 0.333 kg of methanol was added to the autoclave when the additional input amount of TFE reached 6.0 kg and 18.1 kg, respectively. Then, the polymerization was terminated when the additional input amount of TFE reached 40.25 kg. After the polymerization was completed, the unreacted TFE and HFP were released to obtain a wet powder. Then, the wet powder was washed with pure water and dried at 150°C for 10 hours to obtain 44.8 kg of dry powder.
[0192] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of the copolymer. The HFP content and PPVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.
[0193] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. Using the obtained pellets, various physical properties were measured by the above-mentioned methods. The results are shown in Table 3.
[0194] Comparative Example 4
[0195] 945 g of deionized water and 6.9 g of methanol were added to an autoclave with a stirrer of 4 L volume, and the autoclave was fully purged with vacuum nitrogen. Then, the autoclave was vacuum degassed, 945 g of HFP and 12.1 g of PEVE were added to the autoclave in a vacuum state, and the autoclave was heated to 30.0 ° C. Next, TFE was added until the internal pressure of the autoclave reached 0.931 MPa, and then 14.7 g of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.931 MPa, and the set pressure was maintained by continuously adding TFE. 6.9 g of methanol was added 1.5 hours after the start of polymerization. 14.7 g of DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was reduced by 0.001 MPa. 11.3 g was added after 6 hours, and the internal pressure was reduced by 0.001 MPa. Then, 3.0 g of DHP was added every 2 hours until the reaction was completed, and the internal pressure was reduced by 0.001 MPa each time.
[0196] It should be noted that 3.4 g of PEVE was added when the continuous additional amount of TFE reached 190 g and 380 g, respectively. In addition, 6.9 g of methanol was added to the autoclave when the additional amount of TFE reached 140 g. Then, the polymerization was terminated when the additional amount of TFE reached 454 g. After the polymerization was completed, unreacted TFE and HFP were released to obtain a wet powder. Then, the wet powder was washed with pure water and dried at 150°C for 10 hours to obtain 517 g of dry powder.
[0197] The obtained powder is used The copolymer was melt-extruded at 370°C using a screw extruder (manufactured by Imoto Seisakusho Co., Ltd.) to obtain pellets. The HFP content and PEVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.
[0198] After degassing the obtained pellets at 200°C for 8 hours in an electric furnace, they were placed in a portable reactor TVS1 (manufactured by Pressure Glass Industry Co., Ltd.) and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced into atmospheric pressure. 0.5 hours after the introduction of F2 gas, the gas was temporarily evacuated and F2 gas was introduced again. After a further 0.5 hours, the gas was evacuated again and F2 gas was introduced again. Then, the above-mentioned F2 gas introduction and evacuation operations were continued once for 1 hour, and the reaction was carried out at a temperature of 200°C for 8 hours. After the reaction was completed, the reactor was fully replaced with N2 gas, the fluorination reaction was terminated, and pellets were obtained. Using the obtained pellets, various physical properties were measured by the above method. The results are shown in Table 3.
[0199] Comparative Example 5
[0200] 945 g of deionized water and 7.5 g of methanol were added to an autoclave with a stirrer of 4 L volume, and the autoclave was fully purged with vacuum nitrogen. Then, the autoclave was vacuum degassed, 945 g of HFP was added to the autoclave in a vacuum state, and the autoclave was heated to 25.5 ° C. Next, TFE was added until the internal pressure of the autoclave reached 0.840 MPa, and then 29.4 g of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.840 MPa, and the set pressure was maintained by continuously adding TFE. 7.5 g of methanol was added 1.5 hours after the start of polymerization. 29.4 g of DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was reduced by 0.002 MPa. 22.6 g was added after 6 hours, and the internal pressure was reduced by 0.002 MPa. Then, 6.0 g of DHP was added every 2 hours until the reaction was completed, and the internal pressure was reduced by 0.002 MPa each time.
[0201] In addition, when the additional amount of TFE reached 140 g, 7.5 g of methanol was added to the autoclave. Then, when the additional amount of TFE reached 454 g, the polymerization was terminated. After the polymerization was completed, unreacted TFE and HFP were released to obtain a wet powder. Then, the wet powder was washed with pure water and dried at 150° C. for 10 hours to obtain 504 g of dry powder.
[0202] The obtained powder is used The copolymer was melt-extruded at 370°C using a screw extruder (manufactured by Imoto Seisakusho Co., Ltd.) to obtain pellets. The HFP content and PPVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.
[0203] After degassing the obtained pellets at 200°C for 8 hours in an electric furnace, they were placed in a 500ml portable reactor (TVS1 type, manufactured by Pressure Glass Industry Co., Ltd.) and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced into atmospheric pressure. 0.5 hours after the introduction of F2 gas, the gas was temporarily evacuated and F2 gas was introduced again. After a further 0.5 hours, the gas was evacuated again and F2 gas was introduced again. Then, the above-mentioned F2 gas introduction and evacuation operations were continued once for 1 hour, and the reaction was carried out at a temperature of 200°C for 8 hours. After the reaction was completed, the reactor was fully replaced with N2 gas, the fluorination reaction was terminated, and pellets were obtained. Using the obtained pellets, various physical properties were measured by the above method. The results are shown in Table 3.
[0204] Comparative Example 6
[0205] The amount of methanol added before the start of polymerization was changed to 0.019 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.019 kg, the amount of PPVE added before the start of polymerization was changed to 1.34 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.41 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.906 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The obtained pellets were used to measure the HFP content and PPVE content by the above method. The results are shown in Table 3.
[0206] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. Using the obtained pellets, various physical properties were measured by the above-mentioned methods. The results are shown in Table 3.
[0207] Comparative Example 7
[0208] The amount of methanol added before the start of polymerization was changed to 0.216 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.216 kg, the amount of PPVE added before the start of polymerization was changed to 0.38 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.11 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.918 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The obtained pellets were used without fluorination, and various physical properties were measured by the above method. The results are shown in Table 3.
[0209] Example 1
[0210] 40.25 kg of deionized water and 0.246 kg of methanol were added to an autoclave with a stirrer of a volume of 174 L, and the autoclave was fully replaced with vacuum nitrogen. Then, the autoclave was vacuum degassed, 40.25 kg of HFP and 0.57 kg of PPVE were added to the autoclave in a vacuum state, and the autoclave was heated to 25.5 ° C. Next, TFE was added until the internal pressure of the autoclave reached 0.840 MPa, and then 1.25 kg of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.840 MPa, and the set pressure was maintained by continuously adding TFE. 0.246 kg of methanol was added 1.5 hours after the start of polymerization. 1.25 kg of DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was reduced by 0.002 MPa. 0.96 kg was added 6 hours later, and the internal pressure was reduced by 0.002 MPa. Then, 0.25 kg of DHP was added every 2 hours until the reaction was completed, and the internal pressure was reduced by 0.002 MPa each time.
[0211] It should be noted that 0.14 kg of PPVE was added when the continuous additional input amount of TFE reached 8.1 kg, 16.2 kg, and 24.3 kg, respectively. In addition, 0.246 kg of methanol was added to the autoclave when the additional input amount of TFE reached 6.0 kg and 18.1 kg, respectively. Then, the polymerization was terminated when the additional input amount of TFE reached 40.25 kg. After the polymerization was completed, the unreacted TFE and HFP were released to obtain a wet powder. Then, the wet powder was washed with pure water and dried at 150°C for 10 hours to obtain 45.4 kg of dry powder.
[0212] The obtained powder was melt-extruded at 370°C using a screw extruder (trade name: PCM46, manufactured by Ikegai Co., Ltd.) to obtain pellets of the copolymer. The HFP content and PPVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.
[0213] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. Using the obtained pellets, various physical properties were measured by the above-mentioned methods. The results are shown in Table 3.
[0214] Example 2
[0215] The amount of methanol added before the start of polymerization was changed to 0.276 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.276 kg, the amount of PPVE added before the start of polymerization was changed to 0.48 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.13 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.928 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The obtained pellets were used to measure the HFP content and PPVE content by the above method. The results are shown in Table 3.
[0216] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. Using the obtained pellets, various physical properties were measured by the above-mentioned methods. The results are shown in Table 3.
[0217] Example 3
[0218] The amount of methanol added before the start of polymerization was changed to 0.261 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.261 kg, the amount of PPVE added before the start of polymerization was changed to 0.50 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.14 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.918 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The obtained pellets were used to measure the HFP content and PPVE content by the above method. The results are shown in Table 3.
[0219] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. Using the obtained pellets, various physical properties were measured by the above-mentioned methods. The results are shown in Table 3.
[0220] Example 4
[0221] The amount of methanol added before the start of polymerization was changed to 0.220 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.220 kg, the amount of PPVE added before the start of polymerization was changed to 0.34 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.10 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.918 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The obtained pellets were used to measure the HFP content and PPVE content by the above method. The results are shown in Table 3.
[0222] After degassing the obtained pellets at 200°C in an electric furnace for 72 hours, the pellets were placed in a vacuum vibration reactor VVD-30 (manufactured by Ohkawara Manufacturing Co., Ltd.) and heated to 120°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced into atmospheric pressure. 0.5 hours after the introduction of F2 gas, the gas was temporarily evacuated and F2 gas was introduced again. After a further 0.5 hours, the gas was evacuated again and F2 gas was introduced again. Then, the above-mentioned F2 gas introduction and evacuation operations were continued once for 1 hour, and the reaction was carried out at a temperature of 120°C for 7 hours. After the reaction was completed, the reactor was fully replaced with N2 gas, the fluorination reaction was terminated, and pellets were obtained. Various physical properties were measured using the obtained pellets by the above method. The results are shown in Table 3.
[0223] Example 5
[0224] The amount of methanol added before the start of polymerization was changed to 0.178 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.178 kg, the amount of PPVE added before the start of polymerization was changed to 0.26 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.08 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.914 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. The obtained pellets were used to measure the HFP content and PPVE content by the above method. The results are shown in Table 3.
[0225] The obtained pellets were fluorinated in the same manner as in Comparative Example 1. Using the obtained pellets, various physical properties were measured by the above-mentioned methods. The results are shown in Table 3.
[0226] Example 6
[0227] 945 g of deionized water and 3.2 g of methanol were added to an autoclave with a stirrer of 4 L volume, and the autoclave was fully replaced with vacuum nitrogen. Then, the autoclave was vacuum degassed, 945 g of HFP and 4.2 g of PEVE were added to the autoclave in a vacuum state, and the autoclave was heated to 30.0 ° C. Next, TFE was added until the internal pressure of the autoclave reached 0.909 MPa, and then 14.7 g of 8% by mass di(ω-hydroperfluorohexanoyl) peroxide solution (hereinafter referred to as DHP) was added to the autoclave to start polymerization. The internal pressure of the autoclave at the start of polymerization was set to 0.909 MPa, and the set pressure was maintained by continuously adding TFE. 3.2 g of methanol was added 1.5 hours after the start of polymerization. 14.7 g of DHP was added 2 hours and 4 hours after the start of polymerization, and the internal pressure was reduced by 0.001 MPa. 11.3 g was added after 6 hours, and the internal pressure was reduced by 0.001 MPa. Then, 3.0 g of DHP was added every 2 hours until the reaction was completed, and the internal pressure was reduced by 0.001 MPa each time.
[0228] It should be noted that 1.3 g of PEVE was added when the continuous additional amount of TFE reached 190 g and 380 g, respectively. In addition, 3.2 g of methanol was added to the autoclave when the additional amount of TFE reached 140 g. Then, the polymerization was terminated when the additional amount of TFE reached 454 g. After the polymerization was completed, unreacted TFE and HFP were released to obtain a wet powder. Then, the wet powder was washed with pure water and dried at 150°C for 10 hours to obtain 518 g of dry powder.
[0229] The obtained powder is used The copolymer was melt-extruded at 370°C using a screw extruder (manufactured by Imoto Seisakusho Co., Ltd.) to obtain pellets. The HFP content and PEVE content of the obtained pellets were measured by the above-mentioned method. The results are shown in Table 3.
[0230] After degassing the obtained pellets at 200°C for 8 hours in an electric furnace, they were placed in a portable reactor TVS1 (manufactured by Pressure Glass Industry Co., Ltd.) and heated to 200°C. After evacuation, F2 gas diluted to 20% by volume with N2 gas was introduced into atmospheric pressure. 0.5 hours after the introduction of F2 gas, the gas was temporarily evacuated and F2 gas was introduced again. After a further 0.5 hours, the gas was evacuated again and F2 gas was introduced again. Then, the above-mentioned F2 gas introduction and evacuation operations were continued once for 1 hour, and the reaction was carried out at a temperature of 200°C for 8 hours. After the reaction was completed, the reactor was fully replaced with N2 gas, the fluorination reaction was terminated, and pellets were obtained. Using the obtained pellets, various physical properties were measured by the above method. The results are shown in Table 3.
[0231] Next, a reference example of a method for producing a copolymer is shown. The copolymer described in the reference example is not included in the embodiment of the copolymer of the present invention. In addition, the obtained copolymer may also be fluorinated. As a method for fluorination, the same method as in Comparative Example 1 or Example 4 may be cited.
[0232] Reference Example 1
[0233] The amount of methanol added before the start of polymerization was changed to 0.321 kg, the amount of methanol added in batches after the start of polymerization was changed to 0.321 kg, the amount of PPVE added before the start of polymerization was changed to 0.48 kg, the amount of PPVE added in batches after the start of polymerization was changed to 0.14 kg, and the set pressure inside the autoclave before and after the start of polymerization was changed to 0.911 MPa. Copolymer pellets were obtained in the same manner as in Comparative Example 1. Using the obtained pellets, various physical properties were measured by the above-mentioned methods. The results are shown in Table 3.
[0234] [Table 3]
[0235] Table 3
[0236]
[0237] "Others (pcs / C10)" in Table 3 6 The record of "<9" in Table 3 means that the number (total number) of -CF2H groups is less than 9. The record of "<6" in Table 3 means that the number (total number) of the target functional groups is less than 6. The record of "ND" in Table 3 means that the peak for the target functional group cannot be confirmed to a quantitative degree.
[0238] Next, the following properties were evaluated using the obtained pellets. The results are shown in Table 4.
[0239] (Haze value)
[0240] The pellets and a hot press molding machine were used to prepare a sheet having a thickness of about 1.0 mm. The sheet was immersed in a quartz cell filled with pure water using a haze meter (trade name: NDH7000SP, manufactured by Nippon Denshoku Industries Co., Ltd.) in accordance with JIS K 7136 to measure the haze value.
[0241] (150℃ flexural modulus)
[0242] The pellets and the hot press molding machine were used to prepare a sheet test piece with a thickness of 3.2 mm, and a test piece of 80 mm×13 mm was cut out. The obtained test piece was used to measure the bending modulus at 150°C using Autograph AG-I 300 kN (AG-I 300 kN manufactured by Shimadzu Corporation) according to ASTM D790 under the conditions of a support distance of 60 mm and a test speed of 2 mm / min.
[0243] A molded body having a high 150°C flexural modulus is less likely to deform even when a bending load is applied at a high temperature.
[0244] (Storage modulus (E'))
[0245] The dynamic viscoelasticity was measured using DVA-220 (manufactured by IT Measurement and Control Co., Ltd.). As a sample test piece, a thermoformed piece with a length of 25 mm, a width of 5 mm, and a thickness of 0.2 mm was used, and the measurement was performed in the range of 30°C to 250°C under the conditions of a heating rate of 2°C / min and a frequency of 10 Hz, and the storage modulus (MPa) at 70°C was read.
[0246] (Recovery amount)
[0247] The measurement of the restored amount is based on the method described in ASTM D395 or JIS K6262:2013.
[0248] Use pellets and a hot press molding machine to make a molded body with an outer diameter of 13mm and a height of about 8mm. Then, by cutting the obtained molded body, a test piece with an outer diameter of 13mm and a height of 6mm is made. Use a compression device to compress the prepared test piece at room temperature to a compression deformation rate of 25% (that is, compress the test piece with a height of 6mm to a height of 4.5mm). The compressed test piece is fixed in the compression device and placed in an electric furnace at 70°C for 72 hours. Remove the compression device from the electric furnace, cool to room temperature, and then remove the test piece. After the recovered test piece is placed at room temperature for 30 minutes, the height of the recovered test piece is measured, and the recovery amount is calculated by the following formula.
[0249] Recovery amount (mm) = t2-t1
[0250] t1: Height of spacer (mm)
[0251] t2: Height of the test piece removed from the compression device (mm)
[0252] In the above test, t1 = 4.5 mm.
[0253] (Resilience at 70°C)
[0254] The 70°C rebound force was calculated by the following formula from the results of the measurement of the amount of recovery at 70°C and the results of the measurement of the storage modulus at 70°C.
[0255] 70℃ rebound force (MPa) = (t2-t1) / t1×E'
[0256] t1: Height of spacer (mm)
[0257] t2: Height of the test piece removed from the compression device (mm)
[0258] E': Storage modulus at 70°C (MPa)
[0259] A molded body having a large resilience at 70° C. is less likely to deform even when a compressive load is continuously applied for a long period of time.
[0260] (150℃ tensile strength)
[0261] The pellets and a hot press molding machine were used to obtain a 2.0 mm thick test piece (compression molding). A dumbbell-shaped test piece was cut out from the test piece using an ASTM V-type dumbbell, and the obtained dumbbell-shaped test piece was used to measure the tensile strength at 150° C. using an Autograph (AG-I 300 kN manufactured by Shimadzu Corporation) according to ASTM D638 at 50 mm / min.
[0262] A molded body having a high 150°C tensile strength is not easily broken even when a tensile force is applied at a high temperature.
[0263] (Ozone exposure test)
[0264] Use pellets and a hot press molding machine to make a sheet with a thickness of 1 mm, and then cut out 10×20 mm as a sample for ozone exposure test. Connect the ozone gas (ozone / oxygen = 10 / 90 volume %) generated by an ozone generator (trade name: SGX-A11MN (modified), manufactured by Sumitomo Seiki Industries, Ltd.) to a PFA container filled with ion exchange water, add water vapor to the ozone gas by bubbling in the ion exchange water, and then expose the sample to the wet ozone gas at 0.7 liters / minute through the PFA tank containing the sample at room temperature. Take out the sample 105 days after the start of exposure, rinse the surface lightly with ion exchange water, and use a transmission optical microscope to observe the portion 5μm to 200μm deep from the sample surface at a magnification of 100 times, and take a picture together with a standard scale to measure the sample surface every 1mm 2 The number of cracks with a length of 10 μm or more was evaluated according to the following criteria.
[0265] ○: The number of cracks is 10 or less;
[0266] ×: The number of cracks exceeded ten.
[0267] (Crack test by chemical immersion)
[0268] Using pellets and a hot press molding machine, a sheet-like molded body with a thickness of about 2 mm was made. Using a rectangular dumbbell of 13.5 mm × 38 mm, the obtained sheet was punched to obtain 3 test pieces. In the center of the long side of each test piece obtained, a 19 mm × 0.45 mm blade was used to cut the incision according to ASTM D1693. Three notched test pieces and 25 g of dimethyl sulfoxide (DMSO) were placed in a 100 ml portable reactor (TVS1 type, manufactured by Pressure Glass Industry Co., Ltd.), and after heating at 150 ° C for 20 hours in an electric furnace, the notched test piece was taken out. The three obtained notched test pieces were installed in a stress crack test fixture according to ASTM D1693. After heating at 150 ° C for 24 hours in an electric furnace, the incision and its surroundings were visually observed to count the number of cracks.
[0269] ○: The number of cracks is 0;
[0270] ×: The number of cracks is 1 or more.
[0271] (Hydrogen peroxide immersion test)
[0272] Using pellets and a hot press molding machine, a sheet with a thickness of about 0.2 mm was produced to produce a 15 mm square test piece. 10 test pieces and 15 g of a 3 mass % hydrogen peroxide solution were placed in a 50 mL polypropylene bottle, heated at 95° C. for 20 hours in an electric furnace, and then cooled to room temperature. The test piece was taken out from the hydrogen peroxide solution, and TISAB solution (10) (manufactured by Kanto Chemical Co., Ltd.) was added to the remaining hydrogen peroxide solution. The fluoride ion concentration in the obtained hydrogen peroxide solution was measured using a fluoride ion meter. The fluoride ion concentration per unit sheet weight (eluted fluoride ion concentration) was calculated from the obtained measured value according to the following formula.
[0273] Dissolved fluoride ion concentration (mass ppm) = measured value (ppm) × amount of hydrogen peroxide solution (g) / weight of test piece (g)
[0274] (Injection moldability)
[0275] ·condition
[0276] The fluorinated copolymer was injection molded using an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., SE50EV-A), with the barrel temperature set to 385°C, the mold temperature set to 180°C, and the injection speed set to 3mm / s. As a mold, a mold (100mm×100mm×3mmt, film gate, flow length 100mm from the gate) in which HPM38 was plated with Cr was used. The obtained injection molded body was observed and evaluated according to the following criteria. The presence or absence of turbidity was visually confirmed. The presence or absence of surface roughness was confirmed by contacting the surface of the injection molded body.
[0277] 3: The injection molded body is transparent as a whole and the surface is smooth as a whole;
[0278] 2: White turbidity is observed within 1 cm from the mold gate and the surface is smooth overall;
[0279] 1: Cloudiness was observed within 1 cm from the location of the mold gate, and roughness was confirmed on the surface within 1 cm from the location of the mold gate;
[0280] 0: The copolymer was not filled in the entire mold, and a molded product of a desired shape was not obtained.
[0281] (Ammonia permeability)
[0282] Using pellets and a hot press molding machine, a sheet test piece with a thickness of about 0.1 mm was prepared. 2 ) was added with 10g of 29% ammonia water, covered with a sheet test piece, and clamped with a PTFE gasket to tighten and seal. The sheet test piece was brought into contact with ammonia water, kept at a temperature of 37°C for 27 days, and then taken out and the mass loss was measured. The ammonia water permeability (mg·cm / m 2 ).
[0283] Ammonia permeability (mg·cm / m 2 ) = mass loss (mg) × thickness of sheet test piece (cm) / penetration area (m 2 )
[0284] (Wire coating molding)
[0285] use A wire coating molding machine (manufactured by TANABE PLASTIC MACHINERY CO., LTD.) was used to extrusion coat a conductor having a conductor diameter of 0.50 mm with the following coating thickness to obtain a coated wire. The wire coating extrusion molding conditions were as follows.
[0286] a) Core conductor: soft steel wire conductor diameter 0.50mm
[0287] b) Coating thickness: 0.25mm
[0288] c) Diameter of coated wire: 1.00mm
[0289] d) Wire pulling speed: 10m / min
[0290] e) Extrusion conditions:
[0291] · Single screw extruder with barrel diameter = 30mm, L / D = 22
[0292] Die head (inner diameter) / sheet (outer diameter) = 9.0mm / 5.0mm
[0293] The set temperatures of the extruder were: barrel C-1 (320°C), barrel C-2 (350°C), barrel C-3 (370°C), head H (380°C), die head D-1 (380°C), die head D-2 (380°C). The core wire preheating was set to 80°C.
[0294] It was visually confirmed that the covered electric wire was produced without any problem.
[0295] (Film Forming)
[0296] use The film was produced using a T-die using an extruder (manufactured by Imoto Seisakusho). The extrusion molding conditions were as follows.
[0297] a) Winding speed: 1m / min
[0298] b) Roller temperature: 120°C
[0299] c) Film width: 70mm
[0300] d)Thickness: 0.10mm
[0301] e) Extrusion conditions:
[0302] · Single screw extruder with barrel diameter = 14mm, L / D = 20
[0303] Extruder set temperature: barrel C-1 (330°C), barrel C-2 (350°C), barrel C-3 (365°C), T-die head (370°C)
[0304] It was visually confirmed that the film was produced without any problem.
[0305] (Tube Forming)
[0306] use An extruder (manufactured by Tanabe Plastic Machinery Co., Ltd.) was used to extrude a tube having an outer diameter of 10.0 mm and a wall thickness of 1.0 mm. The extrusion molding conditions were as follows.
[0307] a) Die head inner diameter: 25mm
[0308] b) Shaft outer diameter: 13mm
[0309] c) Inner diameter of shaping die: 10.5mm
[0310] d) Traction speed: 0.4m / min
[0311] e) Outer diameter: 10.0mm
[0312] f) Wall thickness: 1.0mm
[0313] g) Extrusion conditions:
[0314] · Single screw extruder with barrel diameter = 30mm, L / D = 22
[0315] Extruder set temperature: barrel C-1 (350°C), barrel C-2 (370°C), barrel C-3 (380°C), head H-1 (390°C), die head D-1 (390°C), die head D-2 (390°C)
[0316] It was visually confirmed that the tube was produced without any problem.
[0317]
Claims
1. A fluorinated copolymer, which is a fluorinated copolymer containing tetrafluoroethylene units, hexafluoropropylene units and fluoro(alkyl vinyl ether) units, wherein: The content of the hexafluoropropylene unit is 8.6% to 11.9% by mass based on the total monomer units. The content of the fluoro(alkyl vinyl ether) unit is 0.5% to 1.9% by mass relative to the total monomer units, and the melt flow rate at 372° C. is 4.6 g / 10 min to 14.4 g / 10 min. The total number of -CF2H, carbonyl-containing terminal groups, -CF=CF2 and -CH2OH is relative to every 10 6 The number of carbon atoms in the main chain is less than 90.
2. The fluorinated copolymer according to claim 1, wherein The content of the hexafluoropropylene unit is 9.1% by mass to 11.0% by mass based on the total monomer units.
3. The fluorinated copolymer according to claim 1 or 2, wherein The content of the fluoro(alkyl vinyl ether) unit is 0.5% by mass to 1.3% by mass based on all monomer units.
4. The fluorinated copolymer according to any one of claims 1 to 3, wherein The melt flow rate at 372°C is 5.1 g / 10 min to 14.0 g / 10 min.
5. The fluorinated copolymer according to any one of claims 1 to 4, wherein The fluoro(alkyl vinyl ether) unit is a perfluoro(propyl vinyl ether) unit. 6 . An injection-molded article comprising the fluorinated copolymer according to claim 1 . 7 . A covered electric wire comprising a covering layer comprising the fluorinated copolymer according to claim 1 .
8. A molded product comprising the fluorinated copolymer according to any one of claims 1 to 5, wherein The molded body is a valve, a joint, a nut, a flow meter, a pipe, a membrane or a wire coating.
Citation Information
Patent Citations
Fluorinated terpolymers
JP1977109588A
Layered body and tube
WO2019220850A1